In situ effect of the combination of fluoridated toothpaste and fluoridated gel containing sodium trimetaphosphate on enamel demineralization - Akabane, Sara [UNESP]; Delbem, Alberto Carlos [UNESP]; Pessan, Juliano [UNESP]; Garcia, Luhana [UNESP]; Emerenciano, Nayara [UNESP]; Gonçalves, Diego Felipe [UNESP]; Danelon, Marcelle [UNESP] (Elsevier, 2018)
Objective This in situ study evaluated the effect of the association of low-F (4500 μg F/g) gel containing TMP and FT (1100 μg F/g) on enamel demineralization. Methods This crossover and double-blind study consisted of five phases of seven days each. Volunteers (n = 12) wore palatal appliances containing four enamel blocks. The cariogenic challenge was performed with 30% sucrose solution (six times/day). Treatments were: placebo toothpaste (PT, no fluoride/TMP); 1100 μg F/g toothpaste (FT); FT + 4500 μg F/g + 5%TMP gel (FT + TMP gel); FT + 9000 μg F/g gel (FT + 9000 gel) and FT + 12,300 μg F/g (FT + Acid gel). After topical application of treatments for one min, two blocks were removed for analysis of loosely bound fluoride (CaF2), calcium (Ca), phosphorus (P) and firmly bound fluoride (FA) formed in enamel. After the seven-day experimental periods, the percentage of surface hardness loss (%SH), integrated subsurface hardness loss (ΔKHN), CaF2, Ca, P and FA retained were determined. Moreover, the biofilms formed on the blocks were analyzed for F, Ca, P and insoluble extracellular polysaccharide (EPS) concentrations. Results FT + TMP gel promoted the lowest%SH and ΔKHN (p < 0.001). The highest concentration of CaF2 formed was observed for the FT + Acid gel (p < 0.001), followed by FT + 9000 gel > FT + TMP gel > FT > PT. CaF2 retained on the blocks was reduced across all groups (p < 0.001). Similar values were observed for the Ca/P/F and EPS in enamel and biofilm for all fluoride groups. Conclusion The association of FT + TMP gel significantly reduced enamel demineralization in situ. Clinical Significance: The association of treatments may be an alternative for patients with high caries risk.
Keywords: Biofilm; Caries; Demineralization; Fluoride